Geoinstitute als außerschulische Lernorte für den Geographieunterricht: Empfehlungen für eine didaktische Gestaltung aus der Evaluation des ersten Kieler Geotages - Hlawatsch, Sylke; Hansen, Klaus-Henning (Journal of Geography Education, 2006)
German earth science research institutes recently have started to offer activities like "open days", "summer schools" and "laboratories" for high school students. They assume that the presentation of research results by scientists and the direct confrontation with samples and analytical instruments rises students' interest in earth sciences. For the schools these offers are an opportunity for cross curricular courses like "system earth", climate change" and "sustainable development" that are part of most German school curriculas. On August 28, 2002 the earth science research institutes of Kiel (a city in northern Germany) organised the "Kieler Geotag" that cover 62 different activities offering all earth science sub disciplines. 546 students attended this day. The majority of students came within an out-of-door activity of their geography class. Because of the variety of the activities and the number of students that participated we regarded the event as typical course for similar acitivities at other places in Germany. An evaluation study was conducted to find out whether the students profited from the activities and how the organisation of such a day could be improved. 363 students and 22 teachers filled questionnaires. Most of the students assured that they profited from the day. However students aged 18-22 gained more than students aged 15-17. Students which attended earth science activities with biological focus profited more than students who attended classes whit a focus on mineralogy, geochemistry, geology or geophysics. The answers to open questions were categorized. They allowed to elaborate recommendations to improve the organisation of out-of-school-learning activities on the side of the research institutes as well as on the side of the schools.